Design of concrete structures - Meyer, Christian (Prentice Hall international series in civil engineering and engineering mechanics, 1996)
This introduction to the principles of concrete mechanics and design focuses on the fundamentals - from very basic, elementary to the very complicated concepts and features an easy-to-follow yet thorough step-by-step design methodology. *emphasizes basic principles of the mechanics aspects of concrete design and avoids explanations of the detail requirements which can be found in the ACI Code and Commentary. *surveys modern design philosophies and features an amply illustrated tour of the world of concrete. *carefully lays out the various design procedures step-by-step - for flexural design, shear design, column design, etc, prepares and encourages students to program procedures for computer solution. Instructors, at their own discretion, can suggest follow-up coding assignment. *goes beyond the traditional description of materials to provide substantive coverage of concrete, current concrete technology, and the durability of materials - especially since many engineers will find themselves repairing, rehabilitating, and strengthening existing structures, rather than designing new ones. *explores the interrelationship between design and analysis - a typical problem area for students, especially in relation to statically indeterminate structures, reviews some structural analysis methods for continuous beams and frames, especially those methods that designers will find useful for checking purposes - e.g., moment distribution, explains how the behavior of structures can be controlled through design decisions. *includes sections on basic plate theory and yield line theory as supplements to the common design procedures of the ACI Code. *contains important optional topics that students can master through self-study after understanding the basics such as torsion, slab design, footings, and retaining walls. *includes many easy-to-follow examples worked out in great detail. *contains a large number of illustrations. *features very carefully designed problem sets that require students to think and appreciate various physical aspects of what they are doing. *contains a comprehensive glossary of terms common in concrete engineering and the construction industry. Definitions are based largely on The Cement and Concrete Terminology Report of ACI Committee 116.